KAJIAN FILOLOGI TERHADAP NASKAH SYARA SHALAWAT KUBRA KARYA KGS. MUHAMMAD AZHARI BIN MAKRUF - Septi Cahyani; Nyimas Umi Kalsum; Fitriah Fitriah (Tanjak: Sejarah dan Peradaban Islam, 1970)
This study raised a manuscript entitled Syarah Shalawat Kubra by Kgs. Muhammad Azhari Makruf who uses Philology studies with Codicological Reviews, so that he is able to describe the physics of this manuscript. The research in this thesis uses qualitative research which raises the following problems: 1. Who is Kgs. Muhammad Azhari Makruf, 2. How is the philological study of the Syarah Shalawat Kubra Manuscript, 3. How is the text editing and analysis of the Syarah Shalawat Kubra Manuscript. This research was conducted in order to find out how the physical condition of the manuscript and to find out the information contained in the Syarah Shalawat Kubra script. In addition, so that it can be an effort to preserve the existing manuscripts in Indonesia. The method used in this study is a single manuscript method, namely manuscript inventory, manuscript description, text editing, and content analysis of the manuscript. The Shalawat Kubra Syarah Manuscript provides information contained in it, namely lightening reckoning, orders to separate children from sleeping, prayers that are not accepted, twenty attributes for Allah, restraining lust, content of shalawat kubra, Qibla, prohibition of being a singer in Islam, ten people who hated by God, the approach of worship in Sufism, and the process of death.